Anemia in Inflammatory Bowel Disease: A Neglected Issue in Comprehensive Inflammatory Bowel Disease Management - Randy Adiwinata; Andrea Livina; Bradley Jimmy Waleleng; Harlinda Haroen; Linda Rotty; Fandy Gosal; Luciana Rotty; Cecilia hendratta; Pearla Lasut; Jeanne Winarta; Andrew Waleleng; Marcellus Simadibrata (Acta Medica Indonesiana)
Anemia is the most common extraintestinal inflammatory bowel disease (IBD) manifestations and is significantly correlated with several adverse impacts such as higher hospitalization rate, relapse rate, surgical intervention requirement, and low quality of life. The prevalence of anemia in IBD patients is greatly varied between reports, which is estimated between 8.8% to 74%. However, studies showed there were still gaps in the screening protocol and anemia treatment in daily practice. Anemia in IBD tends to be an overlooked IBD complication yet significant and must be adequately addressed. Anemia in IBD may be caused by several factors that interplayed, with iron deficiency anemia being the most common etiology. Comprehensive management of anemia in IBD should consist of active screening, evaluation of the etiology, holistic treatment, and follow-up monitoring. Optimization of IBD therapy should be emphasized because it also may improve the anemic condition. A multidisciplinary approach and collaboration are needed to ensure better IBD care.